Formation of a fine polymer structure on a plastic substrate through phase separation of a liquid crystal mixture. Issue 1 (2nd January 2021) - Do, Su-Min; Choi, Tae-Hoon; Huh, Jae-Won; Oh, Seung-Won; Choi, Yeongyu; Yoon, Tae-Hoon
Abstract : Reported herein is a method for the formation of a polymer structure on a plastic substrate through the phase separation of a liquid crystal mixture. Polymer walls can be formed on a specific location through phase separation induced by a spatial differences in elastic energy and electric field intensity. The fabricated polymer walls were observed through various methods. The measured aspect ratio of the fabricated polymer walls was about 12.9, with a 10.3 μm height and a 0.8 μm width.